Determining the interlaminar tensile strength of a SiCf/SiC ceramic matrix composite through diametrical compression testing. Issue 7 (July 2023) - Newton, C.D.; Jeffs, S.P.; Gale, L.; Pattison, S.; Bache, M.R.
Abstract: Interlaminar tensile strength (ILTS) of a SiCf /SiC Ceramic Matrix Composite (CMC) was determined through use of a diametrical compression test of disk geometries, with two geometries are investigated (Φ4.5 and Φ9 mm). Results are correlated with the fracture surface architecture, specifically relating to fibre tows. Due to the stochastic nature of ceramic material systems a Weibull distribution was implemented to understand the characteristic strength and distribution of the data sets for both disk geometries. Overall, a decrease in characteristic ILTS coupled with a narrowed distribution is observed for the Φ9 mm compared the Φ4.5 mm disk geometries due to the repeating unit cell size of the SiCf /SiC CMC under investigation.